Effects of ferro sulphate and carbon tetrachloride in liver of rat - Ngadikun Ngadikun Ngadikun (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2010)
Ferro sulphate (FeSO4) overload and carbon tetrachloride (CCl4) are chemical hepatocarcinogen. Ferro sulphatedisrupts the redox balance of the cell and generates chronic oxidative stress by which modulates signaling networksrelated to malignant transformation. Meanwhile CCl4 induces hepatic damage in lipid peroxidation and decreasesactivities of antioxidant enzymes and generation of free radicals. The aim of this study is to investigate the effect ofa pause of chemical hepatocarcinogen induced in Rattus norvegicus rats. Twomonths old adultmaleRattus norvegicusrats weighing around 110–191 g were used. The ratswere divided into three groups. In group I (n=3), no-treatmentcontrol; in group II (n=3), rats were fed 3.5%FeSO4 in the diet together with 0.1 ml/ kgBWCCl4 administered bygavage per os 5 days a week for 3 weeks. However, in group III (n=3), rats were administered by chemicalhepatocarcinogen like group I then continued with no-treatment for 2 weeks (a pause of 2 weeks was inserted).Body weight were determined per week. At the end of the experiment, rats were fasted overnight, and then 3.0 mlof blood was drawn from the rats from the vena orbitalis in EDTA-tube and then sacrificed. Liver and body weight ofrats were determined for each group. Plasma was prepared to biochemical estimation of different parameters liketotal protein (TP), non-functional plasma enzymes: aspartate aminotransferase (AST), alanine aminotransferase(ALT), and gamma glutamyl transferase (GT) by biochemical test kits in SYNCHRON CX® System(s). The livertissuewas used for histological and immunohistochemical assessment. All datawere analyzedwith one-way ANOVA,p<0.05 for the statistical comparison of groups in Matrix Laboratory (MATLAB) programs in MicrosoftWindowsXP.According to the research results of the body weight on treated group gained significantly less body weight thancontrol group (p= 0.00). Liver weight at the end of the experiment were significantly decreased in treated groupcompared to control (p=0.00); but Liver/ Body weight ratio were significantly increased in treated group comparedto control (p=0.00). The blood plasma were significant differences in the values of TP and GT (p = 0.00 and0.00), but the values of AST, ALT, and ratio of AST to ALT were not significant differences (p=0.62, 0.67, and0.26 respectively). Histopathological studies of the liver section of treated group showed the damage of the livercells. In the group of a pause of chemical hepatocarcinogen induced in rats were no major morphological changeswere observed compared to group that administered for 3 weeks, except for decreased steatosis level. An overalldecrease in vacuoles at the group of a pause suggested a changemetabolismand toxin depletion over time. Furthermore,p53 immunohistochemistry on 9 cases revealed no p53 mutations or protein overexpression. It was concluded thatp-53 mutation was not detected in Rattus norvegicus rats that induced hepatocarcinogenic agent FeSO4 3.5%andCCl4 0.1 ml/ kg BW for 3 weeks and hepatic injury still encountered in a pause of chemical hepatocarcinogeninduced showed that the recovery was not complete.Key words: pause of chemical hepatocarcinogen induced - Rattus norvegicus - liver tissue - total protein - nonfunctionalplasma enzymes